(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article analyzes the stages of the formation and development of veterinary science in Uzbekistan. The veterinary field has been closely related to animal husbandry since ancient times, and its development was shaped by socio-economic and scientific-technical factors. The article covers the initial stages of veterinary service in Uzbekistan, its development on a scientific basis in the 19th-20th centuries, and the formation of the modern veterinary system. Special attention is also paid to the reforms, scientific research, and international cooperation carried out in the veterinary field during the period of independence. This study not only shows the importance of veterinary science in society, but also reveals its future prospects.